2008
DOI: 10.2214/ajr.07.3045
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Mandibular Osteonecrosis Secondary to Bisphosphonates

Abstract: MRI is an effective tool in the assessment of osteonecrosis of the jaw. The significance of focal lesions detectable on radiologic examination but without clinical correlation and their progression over time remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Radiography is usually considered as first-line, while CT and MRI as second-line imaging modalities. MRI may not only help to determine the number and extension of foci, including soft tissue involvement, but also allow for early disease detection [25]. However, major issues were discovered when research studies were performed comparing radiography, CT, MRI, scintigraphy, SPECT-CT and positron emission tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Radiography is usually considered as first-line, while CT and MRI as second-line imaging modalities. MRI may not only help to determine the number and extension of foci, including soft tissue involvement, but also allow for early disease detection [25]. However, major issues were discovered when research studies were performed comparing radiography, CT, MRI, scintigraphy, SPECT-CT and positron emission tomography.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging characteristics of MRI in patients with MRONJ have been described. 26,27 However, owing to its low level of specificity it has limited predictive value for detecting early disease. A recent retrospective study analyzed the utility of PET in MRONJ patients with established disease and reported a low level of sensitivity, specificity, and accuracy, implying limited diagnostic value for this imaging modality.…”
Section: Imagingmentioning
confidence: 99%
“…9) is termed unmasking and should not be confused with progression on treatment (10). Additional MRI findings commonly seen in MM patients include insufficiency fractures, infections, avascular necrosis of the femoral or humeral heads, and osteonecrosis of the maxilla or mandible (3,10,45,46,66).…”
Section: Correlating 18 F-fdg Pet/ct and Mri Of MMmentioning
confidence: 99%